2019
DOI: 10.1089/ten.teb.2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Chronic Wounds: An Update of Recent Developments and Future Possibilities

Abstract: Healing of chronic wounds : an update of recent developments and future possibilities Kathawala,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 174 publications
0
50
0
1
Order By: Relevance
“…[ 6 ] Nonetheless, protein‐based materials of animal origin introduce the risk of xenogeneic infections and adverse immune response. [ 7 ] Moreover, large‐scale production of proteinaceous scaffolds poses an economic conundrum due to limited natural protein sources and the high cost of producing recombinant proteins as a substitute. To address these concerns, a promising solution is to exploit human hair waste as an abundant and renewable source of keratin proteins to develop an autologous biological scaffold.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Nonetheless, protein‐based materials of animal origin introduce the risk of xenogeneic infections and adverse immune response. [ 7 ] Moreover, large‐scale production of proteinaceous scaffolds poses an economic conundrum due to limited natural protein sources and the high cost of producing recombinant proteins as a substitute. To address these concerns, a promising solution is to exploit human hair waste as an abundant and renewable source of keratin proteins to develop an autologous biological scaffold.…”
Section: Figurementioning
confidence: 99%
“…[ 12 ] Specific to dermal wound healing applications, interconnected porosity enables moisture retention, absorption of wound exudates, and gaseous exchange while the 3D structure provides mechanical integrity for dermis restoration. [ 7,13 ] For instance, Wang et al. reported that HHK hydrogels encapsulated with L929 fibroblasts could perform comparably well, relative to collagen hydrogels, in terms of supporting cell proliferation and were better at resisting graft contraction.…”
Section: Figurementioning
confidence: 99%
“…Collagen type I-based hydrogels are the most used substrate when producing skin equivalents (Kim B. S. et al, 2018). A wide range of products and strategies are now available for purposes of skin repair and grafting, toxicology testing and drug development (Shevchenko et al, 2010;Kathawala et al, 2019). Composite hydrogels are growing in popularity for skin regeneration because the native skin matrix is an orchestrated blend of several ECM components including collagen, elastin, fibronectin, vitronectin, glycosaminoglycans, and more.…”
Section: Skinmentioning
confidence: 99%
“…[ 1–2 ] During the long‐time process of skin repair, wound healing is easily interrupted and hindered by some incidents, which may decrease the regenerative effects and disturb the tissue repair. [ 3 ] Particularly on diabetic patients, some chemokines and growth factors irregulating cell functions are extremely constrained to cause a worse recovery. [ 4–5 ] Consequently, skin injury is still a major healthcare problem, especially for the patients with chronic ulcers.…”
Section: Introductionmentioning
confidence: 99%